Plasmonic-Enhanced Organic Light-Emitting Diodes Based on a Graphene Oxide/Au Nanoparticles Composite Hole Injection Layer - Feng, Jiahuan; Sun, Dongwei; Mei, Sijiong; Shi, Wuxing; Mei, Fei; Zhou, Yuanming; Xu, Jinxia; Jiang, Yan; Wu, Linzhang (Frontiers in Materials, 2018)
Organic light-emitting diodes (OLEDs) have drawn a great deal of attention due to their wide application in lighting and displaying. With the development of nanotechnology, surface plasmas have been widely used in photonics, microscopes, solar cells and biosensors. In this paper, by inserting graphene oxide (GO), Au nanoparticles (Au NPs) and GO/Au NPs composite structures between the hole transport layer (NPB) and indium tin oxide (ITO) anode respectively, the electroluminescent performance of Alq3-based OLEDs was significantly enhanced. Compared to the reference devices, the devices with the composite inserting layer containing 10% GO/Au NPs doping have the best electroluminescent performance, which have improved 47.9% in maximum luminance, 49.2% in maximum current efficiency and 45.3% in maximum external quantum efficiency (EQE), respectively. Such substantial enhancement of photoelectric performance can be attributed to the combined effects of LSPR coupling and the better hole transport property by introducing Au NPs and graphene oxide doped layer.